ANALISIS PERATURAN PEMERINTAH NOMOR 28 TAHUN 2024 TENTANG PERATURAN PELAKSANAAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN TERKAIT PEMBERIAN ALAT KONTRASEPSI BAGI SISWA DAN REMAJA - HILALA, PARDI (Ganec Swara, 2025)
Government Regulation No. 28 of 2024 is an implementation of Law No. 17 of 2023 on Health, which focuses on improving health services, particularly in the context of adolescent reproductive health. This study analyzes the main aspects regulated in the regulation, including the implementation of health efforts, management of medical personnel, health service facilities, and health information systems. In addition, this study also explores the extent to which PP No. 28/2024 supports the objectives of the Health Law in improving access and quality of health services in Indonesia. Although this regulation aims to provide protection and education to adolescents regarding reproductive health, there is controversy regarding the provision of contraceptives that can be misinterpreted. Therefore, it is important for the government to conduct effective socialization and provide clear explanations to the public. The results show that the successful implementation of PP No. 28/2024 relies heavily on good communication between the government and the community as well as policy adjustments based on feedback from various parties. With these measures, it is hoped that this regulation can have a positive impact on Indonesia's health system as a whole.